Perancangan Enterprise Architecture Sistem Informasi Menggunakan Framework TOGAF ADM 9.2 PT. XYZ - Mangapul Siahaan (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
PT.XYZ is a gas oil manufacturing company, which produces offshore oil and gas drilling equipment. In supporting its business processes, this company uses a separate module application which causes data flow to be interrupted and results in the company experiencing delays in managing data and getting information on time. Based on the analysis of the problem, the researcher will design an integrated enterprise information system architecture for sales, finance, raw material procurement, production, project plan, and inventory. The method used is the TOGAF ADM 9.2 framework which consists of four phases, namely the vision architecture, business architecture, information system architecture, and technology architecture phases. This enterprise architecture design produces a blueprint as a guideline or framework in the development of information systems at PT. XYZ. The overall result of this research is to produce an enterprise architecture information system design